PEMIKIRAN MUHAMMAD ABDUH: DARI TAKLID BUTA MENUJU NALAR TERBUKA DALAM APLIKASI KONSEP IJTIHAD PADA PEMBELAJARAN DI SDN 01 JATIMULYO - Helmi Handoko; Leny Misdiyanti; Muhammad Fauzi; Abu Mansur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze Muhammad Abduh’s concept of ijtihad and his critique of blind taqlid, as well as to describe the relevance and application of ijtihad principles in the learning process at SDN 01 Jatimulyo. The research employs a qualitative descriptive approach, utilizing interviews, observations, and documentation for data collection. The subjects include the school principal, Islamic Education (PAI) teachers, classroom teachers, and students from grades IV to VI. The findings reveal that Muhammad Abduh’s ideas on ijtihad can be applied in elementary education through the cultivation of critical thinking, rational reasoning, and the avoidance of blind imitation in learning. The relevance of ijtihad is reflected in the curriculum and teaching methods that integrate religious and general sciences, supported by the implementation of Problem Based Learning (PBL) to foster analytical and independent thinking. The application of this concept is a strategic effort to prepare Muslim generations who are spiritually devout, intellectually intelligent, and adaptive to modern challenges.